The Surgical Intervention in Genitourinary Tuberculosis (Bangladesh Journal of Urology, 2020)
Introduction: Genitourinary tuberculosis (GUTB) is the leading cause of morbidity and mortality worldwide especially in developing countries. Surgery is an essential management modality in genitourinary tuberculosis when indicated.Objective: This study aims to document the role of surgery for genitourinary tuberculosis according to the organ involved.Materials and Methods: Retrospective review of 33 GUTB cases was done that underwent surgery at department of urology, Bangabandhu Sheikh Mujib Medical University from January 2008 to December 2014. Patient’s baseline characteristics, mode of presentation, organ involvement, investigation, surgical intervention and follow up were studied.Results: Among enrolled patients, mean age at presentation was 31.5 years and 64% (21, 33) were male. The most common presentation was irritative voiding symptoms. Kidney was the most common organ involved in 39% (13, 33) cases, and next common site was bladder in 30% (10, 33) cases. Preoperative bacteriologic diagnosis was confirmed only in 21% (7, 33) cases. A total of 41 surgical procedures were performed as some patients needed more than one procedure. These included 13 endoscopic, 6 temporary diversion, 19 ablative procedures and 3 reconstructive procedures. Post surgical follow up of all the patients were given after 3, 6 and 12 months. Then the patients were followed with RFT and ultrasonography 6 monthly for 3 years and then annually. The intravenous urography and diethylenetriamine pentaacetic acid scan were performed when indicated.Conclusion: Multidrug chemotherapy with judicious surgery when indicated is the ideal treatment. Surgery plays an important role in symptomatic relief and helps to lead a normal life. The results of reconstructive surgery are good and should be done when possible. Rigorous and long term follow up is necessary in patients undergoing reconstructive surgery.Bangladesh Journal of Urology, Vol. 19, No. 2, July 2016 p.69-73